The concept of intellectual property and ownership right according to islamic jurisprudence / Zanirah Mustafa@Busu ...[et al.]. - Mustafa @ Busu, Zanirah; Awang @ Ab. Rahman, Nurul Hidayah; Nik Din, Nik Muniyati; Noor Zainan, Nurul Izzah; Ismail, Mohd. Khairul Anuar; Mohd Firdaus Kozako, Intan Nurul 'Ain (2021)
Intellectual property is a property that most ordinary people in Malaysia are unconcerned about the law on illegal use of the intellectual property. The use of intellectual property without lawful authorization is an offense that may be subjected to legal action by a responsible party in Malaysia. In Malaysia, the sale of counterfeit CDs or DVDs is so rampant at night markets. Furthermore, many netizens commonly download local or international films from illegal websites on the internet. Therefore, all parties to work together to address this emerging issue by using effective approaches. The main objective of this study was to explain the concept of intellectual property from the perspective of Islamic jurisprudence (fiqh). Additionally, this study identified the degree of position and status of intellectual property rights in Islamic fiqh. Methods of library research, documentation, observations, and research methods are used to collect relevant information. The data collected in this study indicated that most people in Malaysia had abused intellectual property rights. Hence, intellectual property must be protected just like traditional property such as lands or goods. If intellectual property law is not enacted in Islam jurisprudence, the public will indiscriminately and continuously commit piracy, plagiarism, and other violations of intellectual property. Consequently, a concerted effort is required by conducting screening, inspection, or monitoring, and action should be taken at state and international levels. Through literature study and descriptive analysis approach, this journal concludes that if intellectual property rights cause harm to society and the state, especially in the exploitation of material rights, then they have created a monopoly that is detrimental and prohibited.